Charlie and the chocolate factory - Dahl, Roald; Blake, Quentin (New York, N.Y. : Puffin Books, an imprint of Penguin Group (USA), 2013)
Each of five children lucky enough to discover an entry ticket into Mr. Willy Wonka's mysterious chocolate factory takes advantage of the situation in his own way.
5.3
3-6.
3-6
Keywords: Bucket, Charlie (Fictitious character) -- Juvenile fiction; Chocolate factories -- Juvenile fiction; Human behavior -- Juvenile fiction; Wonka, Willy (Fictitious character) -- Juvenile fiction; Behavior -- Fiction; Bucket, Charlie (Fictitious character) -- Fiction; Chocolate factories -- Fiction; Humorous stories; Wonka, Willy (Fictitious character) -- Fiction; Bucket, Charlie (Fictional character) -- Fiction; Chocolate factories -- Fiction; Human behavior -- Fiction; Humorous fiction; Wonka, Willy (Fictional character) -- Fiction; Humorous fiction